Congenital toxoplasmosis the overlooked disease: a case report - Osman, Mahmoud M.; Albadani, Eiman S.; Abdel-Hamid, Suzan; Hamdoun, Sulafa A.; Alruwaished, Naif A. (International Journal of Contemporary Pediatrics, 2021)
The causative agent of congenital toxoplasmosis (CT) is Toxoplasma gondii, an obligate intracellular parasitic protozoan presenting as a zoonotic infection distributed worldwide. Congenital toxoplasmosis may lead to abortion, intrauterine growth restriction, hepatosplenomegaly, jaundice and several neurological and ocular manifestations. The classic pathognomonic manifestations are the triad of intracranial calcifications, hydrocephalus and chorioretinitis. However, the majority of infected infants are asymptomatic at birth. Herein, we reported a case of severe CT in a late preterm newborn. Interestingly, the majority of the manifestations reported for CT were observed in this case. The high anti-toxoplasma antibodies (IgM and IgG) in the infant and his mother confirmed the diagnosis.